ANALISIS KUALITAS FISIK RUMAH DENGAN KEBERADAAN MYCOBACTERIUM TUBERCULOSIS DI UDARA - Elsya Kurniawati; Lilis Sulistyorini (The Indonesian Journal of Public Health, 2018)
Tuberculosis (TB) cases in Indonesia are most prevalent in West Java, East Java, and Central Java Provinces. TB cases in those provinces accounted for 38% of all incident TB cases in Indonesia. Transmission of the disease is influenced by environmental factors and unhealthy behavior. Environmental factors that affect the incidence of TB such as temperature, humidity, and natural lighting. This was an observational research, using case-control study design. Data then compared with the Regulation of Health Minister Republic Indonesia No. 1077 in 2011 about Guideline for Air Sanitation in the Home Space and Decision of Health Minister Republic Indonesia No. 829 in 1999 about Housing Health Requirement. Samples were taken by pusposive sampling with a sample size of 10 houses of pulmonary TB patients and 10 home instead of pulmonary TB patiens. Data collection using observation sheet and measurement. Air sampling using Microbial Air Sampler (MAS), then samplees sent to the laboratory for examination of Mycobacterium tuberculosis bacteria. The result showed that most of the temperature, humidity, natural lighting, wide ventilation, and light intensity in the home of tuberculosis patiens not eligible. Mycobacterium tuberculosis was found in all TB home patients. People should maintain the cleanliness of the house by cleaning the floor with disinfectant and adding ventilation to improve air circulation and the sunlight can enter the room.